2021
DOI: 10.29058/mjwbs.869832
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of Observational Studies in Epidemiology: Turkish Adaptation of STROBE Criteria

Abstract: Sağlık çalışmalarında gözlemsel araştırmalar, yaygın olarak kullanılan yöntemler arasında yer almakta olup, esas olarak kohort, vaka-kontrol ve kesitsel çalışmalar olarak gruplandırılırlar. Gözlemsel çalışmaların nasıl yürütülmesi gerektiğine dair esaslar 1965'li yıllarda tanımlanmış olsa da, günümüzde mevcut gözlemsel çalışmalar göz önüne alındığında, bunların raporlamasında yetersizliklerin olduğu görülmüştür. Bu nedenle gözlemsel çalışmaların raporlanmasına bir standart getirilmesi amacıyla, 2007 yılında bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…There were 19 (27.1%) patients with Stage 2 at the time of diagnosis. The stages of the patients in our study were as follows: 14 (20%) in Stage 1a, 13 Median OS in de novo metastatic patients was shorter than that in those with relapse (p=0.001). The median OS of the patients was 79.5 months.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…There were 19 (27.1%) patients with Stage 2 at the time of diagnosis. The stages of the patients in our study were as follows: 14 (20%) in Stage 1a, 13 Median OS in de novo metastatic patients was shorter than that in those with relapse (p=0.001). The median OS of the patients was 79.5 months.…”
Section: Resultsmentioning
confidence: 68%
“…Our study was designed based on the STROBE criteria. 13 The population of the study comprised 342 (n=342) patients with EC who reported to the Dokuz Eylül University Hospital Medical Oncology outpatient clinic for diagnosis and treatment between 2016 and 2021. One hundred and forty-two patients received treatment for concomitant ovarian cancer.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of the study was to determine the levels of PPFC in native Turkish and Syrian refugee individuals with no children. Study reporting conforms to the STROBE checklist [14] , [15] , [16] .…”
Section: Methodsmentioning
confidence: 99%
“…The Strengthening the Reporting of Observational Studies in Epidemiology was used as the guide for the objective implementation of the observation method. 11,12 THE pOpuLATION AND SAMpLE Of THE STuDY…”
Section: Type and Place Of The Studymentioning
confidence: 99%